2021
DOI: 10.1186/s13023-021-02000-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of epidemiological distribution and outcome of COVID-19 in patients with hereditary hemorrhagic telangiectasia: a nationwide retrospective multi-centre study during first wave in Italy

Abstract: Background Coronavirus Disease 2019 (COVID-19) continues to have a devastating impact across the world. A number of pre-existing common clinical conditions were reported to represent risk factors for more severe COVID-19 outcomes. Hereditary Hemorrhagic Telangiectasia (HHT) is a rare vascular heritable disorders, characterized by complications secondary to visceral Arterio-Venous Malformations. The impact of HHT, as well as for many Rare Diseases (RDs) on infection susceptibility profile and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…Regarding the investigation of poor outcome risk, our data highlight a quite benign course with only the 7% needing hospitalization and 2% requiring intensive-care-unit admission in HHT patients. These results are aligned with our preliminary report, centered on the first wave of pandemic spreading [ 14 ], and seem to provide further evidence that no significant difference is found on hospitalization rates and severe outcomes in HHT patients when compared to general population, despite the potential coexistence of chronic conditions due to HHT-related multisystemic involvement. Although two previous studies in Spanish population suggested a reduced severity of COVID-19 in HHT patients, the hypotheses advocated to explain this apparent weaker COVID-19 severity still lack confirmation as they are based on the HHT-damaged endothelial function and/or HHT-altered angiogenesis, which would impair the SARS-CoV-2 infection-driven macrophage inflammatory response, thus potentially protecting HHT patients from developing the cytokine storm [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Regarding the investigation of poor outcome risk, our data highlight a quite benign course with only the 7% needing hospitalization and 2% requiring intensive-care-unit admission in HHT patients. These results are aligned with our preliminary report, centered on the first wave of pandemic spreading [ 14 ], and seem to provide further evidence that no significant difference is found on hospitalization rates and severe outcomes in HHT patients when compared to general population, despite the potential coexistence of chronic conditions due to HHT-related multisystemic involvement. Although two previous studies in Spanish population suggested a reduced severity of COVID-19 in HHT patients, the hypotheses advocated to explain this apparent weaker COVID-19 severity still lack confirmation as they are based on the HHT-damaged endothelial function and/or HHT-altered angiogenesis, which would impair the SARS-CoV-2 infection-driven macrophage inflammatory response, thus potentially protecting HHT patients from developing the cytokine storm [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…The main strength of our study is that we analyzed, through a nationwide multicentric approach the impact of COVID-19 in HHT patients, collecting several clinical data from 605 patients, which represents an extremely high number given that this is a RD. As noted above, and in our first preliminary survey [ 14 ], estimates on hospitalization rates and outcome risks may suffer from significant recruitment bias, whereas such bias can be minimized, although not completely ruled out, by a nationwide multicenter design.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…[ 11 ] COVID-19 infected HHT patients require prioritized intensive management, including invasive ventilation, compared to the general public. [ 12 ] Contrary to this, in a study by Marcos et al ,[ 13 ] 25 of 138 patients with HHT developed COVID-19 infection with a milder course without raised inflammatory markers and better clinical outcomes.…”
Section: Discussionmentioning
confidence: 96%